2006
DOI: 10.1111/j.1460-9568.2005.04566.x
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex NMDA receptors and nitric oxide modulate the parasympathetic component of the baroreflex

Abstract: The ventral portion of the medial prefrontal cortex (vMPFC) is involved in the modulation of the parasympathetic component of the baroreflex. In the present study, we verified the effect of blockade of vMPFC glutamatergic receptors and nitric oxide synthases (NOS) on the parasympathetic component of baroreflex in awake rats. Bilateral microinjection of the non-selective ionotropic glutamate antagonist kynurenic acid (KYN) into the vMPFC caused a shift of the threshold of reflex bradycardia toward higher pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 54 publications
2
33
0
3
Order By: Relevance
“…Increased sympathoadrenal tone 21 with subsequent release of renin and vasoconstriction of arterioles results from (1) direct injury to inhibitory or modulatory brain regions or (2) indirect effects of reduced parasympathetic activity, 22 which leads to impaired cardiac baroreceptor sensitivity in patients with stroke. 23 Although direct injury is the most likely explanation, an indirect effect of muscle paralysis 24 or the release of neurotransmitters such as nitric oxide 25 during ischemia may be contributing factors to altered activity of these nuclei. Other stress responses to hospitalization, headache, urinary retention, or concomitant infection 26 may lead to abnormal autonomic activity and raised levels of circulating catecholamines 27 and inflammatory cytokines 12 and subsequently may contribute to the hypertensive response.…”
Section: Underlying Causes Of Acute Hypertensive Responsementioning
confidence: 99%
“…Increased sympathoadrenal tone 21 with subsequent release of renin and vasoconstriction of arterioles results from (1) direct injury to inhibitory or modulatory brain regions or (2) indirect effects of reduced parasympathetic activity, 22 which leads to impaired cardiac baroreceptor sensitivity in patients with stroke. 23 Although direct injury is the most likely explanation, an indirect effect of muscle paralysis 24 or the release of neurotransmitters such as nitric oxide 25 during ischemia may be contributing factors to altered activity of these nuclei. Other stress responses to hospitalization, headache, urinary retention, or concomitant infection 26 may lead to abnormal autonomic activity and raised levels of circulating catecholamines 27 and inflammatory cytokines 12 and subsequently may contribute to the hypertensive response.…”
Section: Underlying Causes Of Acute Hypertensive Responsementioning
confidence: 99%
“…50 The defensive responses elicited by the CS in animals are characterized by freezing (complete immobility except as required for breathing), reflex expression (characterized by fear-potentiated startle), and autonomic (increase in heart rate and in the mean arterial pressure) and endocrine (stress-related hormone release) responses. [50][51][52][53] Fear conditioning models involve the encoding of traumatic memories, representing a psychological stress without physical stimuli. 51,54 They have been associated with a vulnerability to phobic fears and other anxiety-related disorders, such as panic disorder (PD), agoraphobia, and posttraumatic stress disorder (PTSD).…”
Section: Fear Conditioningmentioning
confidence: 99%
“…Furthermore, a previous study from our group showed that local injection of L-glutamate into the vMPFC evokes an activation of both sympathetic and parasympathetic activities on the heart of unanesthetized rats (48). Moreover, the glutamatergic system present in the vMPFC is involved in baroreflex modulation (45).…”
mentioning
confidence: 99%